Humid heat equally impairs maximal exercise performance in elite para-athletes and able-bodied athletes - Alkemade, P.; de Korte, J. Q.; Bongers, C. C. W. G.; Daanen, H. A. M.; Hopman, M. T. E.; Janssen, T. W. J.; Eijsvogels, T. M. H. (Medicine & Science in Sports & Exercise, 2023)
Purpose This study aimed to compare the impact of hot-humid environmental conditions on performance outcomes, thermoregulatory responses, and thermal perception during exercise between elite para- and able-bodied (AB) athletes.